Physics with post-accelerated beams at ISOLDE: nuclear reactions. (10th March 2017) - Pietro, A Di; Riisager, K; Duppen, P Van
Abstract: Nuclear-reaction studies have until now constituted a minor part of the physics program with post-accelerated beams at ISOLDE, mainly due to the maximum energy of REX-ISOLDE of around 3 MeV/u that limits reaction work to the mass region below A = 100. We give an overview of the current experimental status and of the physics results obtained so far. Finally, the improved conditions given by the HIE-ISOLDE upgrade are described.